CLINICAL SPECTRUM OF DISEASE IN NEONATES BORN TO MOTHERS WITH COVID-19 IN A TERTIARY CARE HOSPITAL - ZAHRA, M; MUNIR, A; CHOUDHRY, S; NAZIR, A; KHAN, EA; KHAN, O; AHMED, O (Biological and Clinical Sciences Research Journal, 2024)
COVID-19 infection during pregnancy presents potential risks to neonates, yet the full clinical spectrum in newborns born to COVID-19-positive mothers remains under investigation. Understanding the clinical outcomes in these neonates is essential for guiding management and care. Objective: To study the spectrum of clinical presentations in neonates born to mothers who tested positive for COVID-19. Methods: This prospective cross-sectional study was conducted at the Department of Pediatrics, Shifa International Hospital, from April 1, 2020, to April 30, 2021. All neonates born to COVID-19-positive mothers were included in the study and followed daily during their hospital stay. After obtaining parental consent, nasopharyngeal swabs were taken from the neonates for SARS-CoV-2 PCR testing at 24-48 hours of age. After discharge, follow-up calls were made between days 7-14. Data were entered into a predesigned proforma and analyzed using SPSS version 23. Results: A total of 82 neonates were enrolled. Approximately half were born at term, with a mean weight of >2500 grams. Forty-five neonates (53%) underwent SARS-CoV-2 PCR testing within 48 hours of age; all were negative. Sixty-one neonates (74%) were shifted to the mother’s care, while 25% required admission to the neonatal intensive care unit (NICU). The most common reasons for NICU admission included respiratory distress (15%), prematurity (6%), and lethargy (5%). Radiological findings included ground-glass appearance in five neonates (6%) and lung consolidation or infiltrates in two (3%). Hematological and biochemical abnormalities included leukocytosis (7%), leucopenia (3.6%), anemia (1.2%), metabolic acidosis (6%), and respiratory acidosis (3.6%). Most neonates (78.6%) received routine care and were fed breast milk. Fourteen neonates (16.7%) required respiratory support, with 13% needing mechanical ventilation. Complications included pneumonia (7%) and respiratory failure (9%). NICU stay varied, with 11 neonates (13%) staying less than 48 hours and 10 (12%) requiring a more extended stay. Four neonates (5%) died due to multiorgan complications. Conclusion: The majority of neonates born to COVID-19-positive mothers remained asymptomatic. However, symptomatic neonates were at risk of serious complications, requiring close monitoring and management, particularly in those with additional risk factors.